2013
DOI: 10.9790/0837-0823540
|View full text |Cite
|
Sign up to set email alerts
|

Effective teaching strategies to encourage learning behaviour

Abstract: Getting pupils' attention as a way to engage them in learning activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The findings of this study may also be associated with teachers' attitudes towards teaching and learning (Awang, Ahmad, Wahab & Mamat, 2013). Effective practical implementation is determined by teachers' ability in guiding students to perform the experiment and students' ability to translate scientific knowledge in practical until there is a balance between the teacher as mentor and students as the learning subjects.…”
Section: Competency In Implementing Chemistry Practicalmentioning
confidence: 93%
“…The findings of this study may also be associated with teachers' attitudes towards teaching and learning (Awang, Ahmad, Wahab & Mamat, 2013). Effective practical implementation is determined by teachers' ability in guiding students to perform the experiment and students' ability to translate scientific knowledge in practical until there is a balance between the teacher as mentor and students as the learning subjects.…”
Section: Competency In Implementing Chemistry Practicalmentioning
confidence: 93%
“…Rahimi and Karkami (2015) stated that teachers commonly use reward strategies in general and praise, in particular, to elude reprimand and violence strategies since these types of strategies have a destructive impact on their motivation and commitment. The study conducted by Awang et al (2013) indicated that teachers praise is a common management strategy that is used in the classroom to manage behavior and upsurge student learning engagement in the classroom.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The appropriate learning strategies, particularly in language learning, will result in students ‗success in learning (Awang et al, 2013). It means deciding which learning strategy that suits best for students is essential.…”
Section: Introductionmentioning
confidence: 99%